2015
DOI: 10.4196/kjpp.2015.19.1.29
|View full text |Cite
|
Sign up to set email alerts
|

ERK Activation by Fucoidan Leads to Inhibition of Melanogenesis in Mel-Ab Cells

Abstract: Fucoidan, a fucose-rich sulfated polysaccharide derived from brown seaweed in the class Phaeophyceae, has been widely studied for its possible health benefits. However, the potential of fucoidan as a possible treatment for hyperpigmentation is not fully understood. This study investigated the effects of fucoidan on melanogenesis and related signaling pathways using Mel-Ab cells. Fucoidan significantly decreased melanin content. While fucoidan treatment decreased tyrosinase activity, it did not do so directly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Song et al . reported that this sulphated polysaccharide from phaeophyte Fucus vesiculosus downregulated melanin synthesis via the activation of the extracellular signal‐related kinase (ERK) pathway, which has been shown to cause the degradation of microphthalmia‐associated transcription factor – which is involved in melanin production . This was shown using Mel‐Ab cells – a murine melanocyte cell line which is particularly efficient in producing melanin .…”
Section: Anti‐pigmentation Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al . reported that this sulphated polysaccharide from phaeophyte Fucus vesiculosus downregulated melanin synthesis via the activation of the extracellular signal‐related kinase (ERK) pathway, which has been shown to cause the degradation of microphthalmia‐associated transcription factor – which is involved in melanin production . This was shown using Mel‐Ab cells – a murine melanocyte cell line which is particularly efficient in producing melanin .…”
Section: Anti‐pigmentation Moleculesmentioning
confidence: 99%
“…Fucoidan, also a phaeophyte secondary metabolite, has been documented as a potential anti‐pigment treatment, with evidence for its mechanism of indirect melanogenesis inhibition , but has not yet been pursued as a cosmetic ingredient. Song et al .…”
Section: Anti‐pigmentation Moleculesmentioning
confidence: 99%
“…Several depigmenting compounds showed antimelanogenic activity via ERK‐mediated downregulation of MITF. For instance, Eucalyptus camaldulensis flower EO, Artocarpus communis extracts, geranylgeranylacetone (C 23 H 37 O), menadione (C 11 H 8 O 2 ), β‐lapachone (C 15 H 14 O 3 ), fucoidan, Withania somnifer, dipeptides (proline‐serine [C 8 H 16 O 5 N 2 ] and valine‐serine [C 8 H 18 O 5 N 2 ]) inhibit melanogenesis through downregulating of MITF via ERK signaling pathways as demonstrated using various cell line models (ie, B16F10, Mel‐Ab cells, human epidermal equivalents [HEE], and Melanoderm™) . E camaldulensis EO and aglycone of Rh 4 differ from other depigmenting compounds in which they also downregulate protein kinase A (PKA) where E camaldulensis EO but not aglycone of Rh 4 also regulates mitogen‐activated protein kinases p38 (p38 MAPK) .…”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%
“…Specific bioactive compounds in W somnifer extract responsible for such action are forthcoming topic of interest for further evaluation. On the other hand, it was suggested that compounds such as oleoylethanolamide (C 20 H 39 NO 2 ), lysophosphatidic acid (C 21 H 41 O 7 P), Zeolite‐4A, C2‐ceramides (C 19 H 37 NO 3 ), sphingosylphosphorylcholine (C 23 H 49 N 2 O 5 P), betulinic acid (C 30 H 48 O 3 ), c‐phycocyanin (C 32 H 45 O 6 N 4 ), and fucoidan (fucose‐rich sulfated polysaccharide) were capable of reducing melanin synthesis by either inducing MITF degradation or blocking MITF expression, via AKT (protein kinase B) and/or ERK pathway …”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%
See 1 more Smart Citation